Quantification and characterisation of porosity in selectively laser melted Al–Si10–Mg using x-ray computed tomography - Maskery, Ian; Aboulkhair, N.T.; Corfield, M.R.; Tuck, Christopher; Clare, A.T.; Leach, Richard K.; Wildman, Ricky D.; Ashcroft, Ian; Hague, Richard J.M. (Elsevier, 2016)
We used X-ray computed tomography (CT), microscopy and hardness measurements to study Al–Si10–Mg produced by selective laser melting (SLM). Specimens were subject to a series of heat treatments including annealing and precipitation hardening. The specimen interiors were imaged with X-ray CT, allowing the non-destructive quantification and characterisation of pores, including their spatial distribution. The specimens had porosities less than 0.1%, but included some pores with effective cross-sectional diameters up to 260 μm. The largest pores were highly anisotropic, being flat and lying in the plane normal to the build direction. Annealing cycles caused significant coarsening of the microstructure and a reduction of the hardness from (114 ± 3) HV, in the as-built state, to (45 ± 1) HV, while precipitation hardening increased this to a final hardness of (59 ± 1) HV. The pore size and shape distributions were unaffected by the heat treatments. We demonstrate the applicability of CT measurements and quantitative defect analysis for the purposes of SLM process monitoring and refinement.